DAMPAK PRODUK DOMESTIK BRUTO DAN INFLASI TERHADAP POTENSI KEBANGKRUTAN UKM DI KOTA SIDOARJO - Indayani, Lilik; Adelia, Wahyu (Universitas Muhammadiyah Yogyakarta, 2019)
This research is raining to know the impact of GDP and Inflation on Potential Bankruptcy of SMEs in Sidoarjo City. The analysis technique used in this research is binary logistic regression analysis which is one of analysis in logistic regression technique. Because in this study the dependent variable using dummy variables expressed in the value 0 (zero) = unhealthy SME / bankruptcy potential and value 1 (one) = Healthy SME / not potentially bankrupt. The result of this research is GDP influence on potential bankruptcy of SMEs in Sidoarjo City. The effect of GDP on the potential bankruptcy of SMEs has a value of P value wald test of 5.059 with a significance value <0.05 means that GDP variables have a significant effect on the potential bankruptcy. And Inflation affects the potential bankruptcy of SMEs in Sidoarjo City Influence of inflation on potential bankruptcy of SMEs has a value of P value of wald test of 6.002 with a significance value <0.05, meaning inflation has a significant effect on the potential bankruptcy. Inflationary influence on the potential for bankruptcy is negative and the potential for bankruptcy is also negative.